Peningkatan Laju Disolusi Dispersi Padat Amorf Genistein dengan PVP K-30 - Erizal Zaini; Vike Zulia Putri; Maria Dona Octavia; Friardi Ismed (Jurnal Sains Farmasi & Klinis, 2017)
Amorphous solid dispersions of a poorly water-soluble drug genistein in PVP K-30 were prepared by solvent co-evaporation technique using organic solvent methanol. Solid dispersions system was prepared with several variations of drug to polymer 2:1, 1:1 dan 1:2 w/w. Solid state properties of solid dispersion system were evaluated by powder X-ray diffraction, Fourier transform infrared spectroscopy, and differential scanning calorimetry, and microscopic SEM. Dissolution rate profile were conducted in distilled water medium by using dissolution tester apparatus type II USP. Base on X-ray diffractometry analysis, differential scanning calorimetry and microscopic SEM, crystalline phase of genistein decreased in crystallinity index and formation of amophous state. Dissolution rate profile showed that genistein in amorphous solid dispersion had a faster dissolution rate in comparison to intact genistein. This study proved that preparation of solid dispersion of genistein in PVP K-30 is an effective approach to improve dissolution rate of genistein.